PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN BATANG NAPIER UNTUK PADA MATA PELAJARAN MATEMATIKA MATERI PERKALIAN BILANGAN CACAH KELAS V DI SEKOLAH DASAR - Hidayah, Nabila Sam; Cahyadi, Fajar; Sundari, Riris Setyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was motivated by the lack of use of learning media during the learning process, the lack of interest of grade V students in learning mathematics and and teachers who still use the lecture method. Students tend to be less active when participating in learning activities and have difficulty in understanding learning materials. Therefore, the development of concrete and interactive learning media is carried out, namely the multiplication napier bar board media. The purpose of this study was to determine how the development of napier bar board media on multiplication material and the feasibility of developing napier bar board media related to multiplication material. This type of research is research and development (R&D) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research consisted of teachers and grade V students totaling 27 students. The data collection techniques used were observation, interview, and questionnaire. The results of the research were obtained from media experts, material experts, teachers and fifth grade students. The results of material validation amounted to 94.5% (very feasible) and the results of learning media validation amounted to 95% (very feasible). The results of the teacher response questionnaire obtained a percentage value of 98.3% (very practical) and the results of the student response questionnaire obtained a percentage value of 100% (very practical). This it can be concluded that the learning media of the multiplication napier bar board is feasible to use as learning media.